A National Online Survey of South Korean High School Students' Understanding of Learning Disabilities. (February 2019) - Lee, Okin; Shin, Mikyung
The purpose of this online survey study was to obtain basic information about South Korean high school students' understanding of learning disabilities. A total of 343 students responded to questions about demographics, familiarity with terms related to learning disabilities, beliefs about learning disabilities, and attitudes toward students with learning disabilities. The study's findings showed that 91.3% of respondents were aware of the term "dyslexia, " yet only 65% had previously heard the term "learning disabilities." The results of chi-square tests indicated that, in general, familiarity with terms related to learning disabilities led to no significant differences in beliefs and attitudes toward students with learning disabilities. However, more respondents who had previously heard the term "learning disabilities" believed that learning disabilities would affect adulthood activities than did those who had never previously heard the term ( p < .05).